Adsorption Studies of Methyl Tert-butyl Ether from Environment. Issue 4 (2nd October 2017) - Vakili, Mohammadtaghi; Rafatullah, Mohd; Salamatinia, Babak; Ibrahim, Mahamad Hakimi; Ismail, Norli; Abdullah, Ahmad Zuhairi
Abstract : The widespread use of methyl tert-butyl ether (MTBE) as a gasoline oxygenate additive has resulted in the presence of MTBE in the environment. This compound is considered as one of the main components of water pollution. Adsorption has received a lot of attention for the removal of MTBE from water. This review paper summarizes the results of adsorption feasibility of different adsorbent for the elimination of MTBE from aqueous solutions. It also discusses the major research topics related to MTBE removal by widely used adsorbents namely, granular activated carbon, minerals, resins and composites. Better understanding of these adsorbents and their affinity toward MTBE adsorption can help future research to be properly oriented to address knowledge gaps in this area. This review provides an opportunity for researchers to explore the removal functionality of MTBE by adsorption methods, better.